The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4318/tjg.2012.0554
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for higher anti-HCV positivity in a border city in southern Turkey with unique population characteristics

Abstract: p= 0.0001) ve e¤itimsizlerde (5.0%) (OR:2.7, p=0.021)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Another study conducted by Ozer et al . found that anti-HCV positivity was higher in married patients [ 20 ]. The seroprevalence of HCV in smaller groups in different parts of Turkey was shown to range between 0 and 3.9% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Ozer et al . found that anti-HCV positivity was higher in married patients [ 20 ]. The seroprevalence of HCV in smaller groups in different parts of Turkey was shown to range between 0 and 3.9% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Türkiye Hepatitis Prevalence (TURKHEP) study reported a nationwide seroprevalence of 1%, some regions have results as high as 3.1% (25,26). Prevalence increases after the age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, which is related to risk factors of hepatitis, C in a border city of Southern Anatolia in Turkey it was found that risk factors might vary compared to overall country. Previous dental procedures and working abroad in neigbouring countries seem to play a role in this difference [14]. In a study related to healthcare associated risk factors for Chronic Hepatitis C infection in Korea it was observed that having multiple sex partners play a minor role in transmission [15].…”
Section: Discussionmentioning
confidence: 99%